Ready, set, go! : - Pavkov, Thomas W. (McGraw-Hill, 2009)
This guide features concise instructions for accessing and using SPSS for Windows. Through ten guided assignments, students learn about statistical analysis of data while also learning the steps in the research process. The students are guided through assignments such as using frequency distributions, performing the t test, using the one-way ANOVA procedure, computing a correlation, and computing chi-square function.